Alternative calcium source effects on commercial egg production and quality - Pelicia, K. [UNESP]; Garcia, Edivaldo Antonio [UNESP]; Scherer, M. R. S. [UNESP]; Mori, C. [UNESP]; Dalanezi, J. A. [UNESP]; Faitarone, A. B. G. [UNESP]; Molino, A. B.; Berto, Dirlei Antonio [UNESP] (Facta-fundacio Arnco Ciência Tecnologia Avicolas, 2007)
This study aimed at verifying the possibility of replacing calcitic limestone by marine calcium in the diet of layers. A total number of 321 Hi-sex hens, with 40 weeks of age at the beginning of the experiment, was used. A completely randomized experimental design was applied, with 5 treatments (0, 15, 30, 45, and 60 % of calcitic limestone replacement by marine calcium source) and eight replicates of eight birds each. Treatments significantly affected specific gravity (p<0.05), with the inclusion of 60% marine calcium (T5) presenting the worst result as compared to T1, which included only calcitic limestone as calcium source. It was concluded that marine calcium can replace up to 45% of calcitic limestone with no effects on performance or egg quality.
Keywords: alternative calcium source; eggshell quality; limestone replacement; marine algae; marine calcium